Design and examination of psychometric features of sports intelligence measurement tool - sara abbasi; Enayatollah Zamanpour; saeed Arsham (مجله علوم روانشناختی, 2025)
Background: Sports intelligence refers to the capacity for effectively processing and responding to environmental stimuli, a crucial ability, especially in high-performance sports. It encompasses components such as reaction time, attention, accuracy, multitasking skills, and mental flexibility. Numerous studies have highlighted the importance of these components in athletic success; however, existing assessment tools only evaluate limited aspects of sports intelligence and do not comprehensively measure the multifaceted abilities of athletes in dynamic conditions. This research gap underscores the need to develop a comprehensive, psychometrically sound tool that can provide a nuanced understanding of athletes' cognitive and functional abilities through multidimensional assessment. Thus, the design and psychometric evaluation of such a tool could lead to valid criteria for assessing sports intelligence and improving athletic performance. Aims: This study aimed to examine the factor structure and psychometric properties of a sports intelligence assessment tool among athletes and non-athletes. Methods: This descriptive-analytical study employed a tool-development approach. The study population comprised all athletes and non-athletes aged 16 to 55 in Alborz Province in 2022. Using convenience sampling, 624 participants were selected. In addition to the sports intelligence tool, the Cattell Intelligence Test (1961) was also administered. Data were analyzed using SPSS version 27 and R version 4.0.2, employing exploratory factor analysis, Pearson correlation coefficient, Cronbach’s alpha, McDonald’s omega, and intraclass correlation coefficients. Results: Exploratory factor analysis indicated that the sports intelligence tool consists of five factors. Furthermore, a significant positive correlation was observed between the dimensions of sports intelligence and the Cattell Intelligence Test (p< 0.05), suggesting suitable criterion validity for the tool. The instrument’s reliability was demonstrated through Cronbach’s alpha values above 0.7 for each of the five factors, indicating high internal consistency. Conclusion: The findings of this study suggest that the sports intelligence tool has satisfactory validity and reliability, making it suitable for assessing sports intelligence in individuals aged 16 to 55.